Antibody reactive to a novel autoantigen on the nondesmosomal keratinocyte surfaces leads to herpetiform pemphigus. (2nd January 2019) - Yuan, H.; Pan, M.
Abstract : Linked Article: Ishiura et al. Br J Dermatol 2019;180 :187–92 .